2012
DOI: 10.1258/td.2012.120062
|View full text |Cite
|
Sign up to set email alerts
|

Maternal mortality in northern Nigeria: findings of a health and demographic surveillance system in Zamfara State, Nigeria

Abstract: The aim of this study was to estimate: (1) the lifetime risk (LTR) of maternal death; and (2) the maternal mortality ratio (MMR) in the Zamfara State of northern Nigeria. Data from the Nahuche Health and Demographic Surveillance System were utilized using the 'sisterhood method' for estimating maternal mortality. Female respondents (15-49 years) from six districts in the surveillance area were interviewed, creating a retrospective cohort of their sisters who had reached the reproductive age of 15 years. Based … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
32
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(34 citation statements)
references
References 9 publications
2
32
0
Order By: Relevance
“…The persistently high rates of maternal mortality in Nigeria are even more stark when the rates are disaggregated by political zone [2], [3]. Estimates from several studies were collated and are presented in Table 2, to illustrate variations in the picture of mortality patterns in the country [4], [5], [6], [7], [8], [9], [10]. For example, the rate is 1049 per 100,000 live births in Zamfara State [8] and 1500/100,000 live births in Sokoto State [7].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…The persistently high rates of maternal mortality in Nigeria are even more stark when the rates are disaggregated by political zone [2], [3]. Estimates from several studies were collated and are presented in Table 2, to illustrate variations in the picture of mortality patterns in the country [4], [5], [6], [7], [8], [9], [10]. For example, the rate is 1049 per 100,000 live births in Zamfara State [8] and 1500/100,000 live births in Sokoto State [7].…”
Section: Introductionmentioning
confidence: 99%
“…Estimates from several studies were collated and are presented in Table 2, to illustrate variations in the picture of mortality patterns in the country [4], [5], [6], [7], [8], [9], [10]. For example, the rate is 1049 per 100,000 live births in Zamfara State [8] and 1500/100,000 live births in Sokoto State [7]. Some locality estimates based on hospital records showed a rate as high as 2,397 per 100,000 live births for the South East, Nigeria, although hospital-based rates are typically higher than population-based rates [4].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The 2008 Nigeria Demographic and Health Survey (NDHS) reported that of all home deliveries, one in five pregnant women delivered alone with no one present [16] . Similar studies have also documented that newborns were five times more likely to die if they had no attendance at birth, three times more likely to die if their births were attended by Traditional Birth Attendants (TBA), and four times more likely to die if they were delivered outside the health facility [17] .…”
Section: Introductionmentioning
confidence: 79%
“…Evidence has shown that neonates were five times more likely to die without a birth attendant, three times more likely to die from births attended by Traditional Birth Attendants (TBA). Births that were delivered outside the health facilities were four times more likely to die [11]. Infants delivered with unskilled birth attendants were four times more likely to develop permanent congenital and early hearing loss (PCEHL) than those delivered with skilled attendance [12].…”
Section: Introductionmentioning
confidence: 99%